The role of emotional tears in intergroup bias - Pang, James, Zhen Yao (2019)
The study of intergroup relations has been a widely researched area in the field of social psychology. Many researchers have delved specifically into the study of intergroup bias, investigating the differences in attitudes, behaviours and stereotypes towards the in-group versus outgroup on the group and member level respectively. Research on emotional tears have suggested interpersonal functions such as facilitation of attachment towards a crier. However, there is a lack of research investigating potential difference when the crier either belongs to an in-group or outgroup. This study aims to investigate the role of tears in intergroup bias. Participants (n = 50) were full-time undergraduates from Nanyang Technological University. This study used the Implicit Association Test to measure implicit intergroup bias. Operationalisation of in-group and outgroup concepts was based on university affiliation. Findings supported that implicit intergroup bias favouring the in-group was present in both non-tear (p = .038) and tear (p = .003) conditions. However, there was no significant difference between participants’ response to in-group or outgroup members. This study broadens the current literature on intergroup bias by investigating the role of tears. Furthermore, in today’s globalised world, the unprecedented ease of travelling brings about influx of foreigners in many countries. As such, intergroup relations and bias are important areas of research as they provide invaluable insights on how humans interact when there is difference in ingroup/outgroup status. Keywords: intergroup relations, intergroup bias, tears, IAT, implicit measures